Strategies for Coping with Pain in Chronic Sciatica in Patients Treated in Neurological Outpatient Clinic - Ewelina Bąk; Iga Wójtowicz; Zofia Nowak-Kapusta (Kazimierz Wielki University, 2018)
Introduction: Back pain is one of the most common causes of deterioration of the psychophysical condition in people. The pain becomes a source of stress for patients and that is why they activate strategies to cope with it. These are the behaviours that patients undertake independently in difficult situations. The aim of this paper was to learn strategies for coping with sciatic pain using the example of patients of the Neurological Outpatient Clinic. Materials and methods: The research was carried out by means of diagnostic survey. The research tools were as follows: own questionnaire, Coping with Pain Strategy questionnaire. The research was carried out among patients of the Outpatient Neurological Clinic BCO of the City Hospital named after John Paul II in Bielsko-Biała in the period from March to September 2017. Before the beginning of the study, the consent of the director of the BCO Municipal Hospital named after John Paul II in Bielsko-Biała was obtained to carry out the research. Findings: The strategies of coping with pain which the respondents chose most frequently were increased behavioural activity, declared coping and diverting attention, the patients were least likely to choose the catastrophizing strategy, re-evaluating pain and ignoring the sensations. Conclusions: Among the strategies for coping with pain in patients with sciatica, the behavioural strategy was dominant, i.e. increased behavioural activity, then the respondents chose the cognitive techniques: declared coping and diverting attention. The type of strategies implemented was influenced by: the time elapsed from the diagnosis of sciatica, the severity of pain and sex of the patient. Keywords: chronic sciatica, strategies for coping with pain, chronic disease.